Purifying stem cell‐derived red blood cells: a high‐throughput label‐free downstream processing strategy based on microfluidic spiral inertial separation and membrane filtration - Guzniczak, Ewa; Otto, Oliver; Whyte, Graeme; Chandra, Tamir; Robertson, Neil A.; Willoughby, Nik; Jimenez, Melanie; Bridle, Helen (Biotechnology and bioengineering, 2020)
Cell‐based therapeutics, such as in vitro manufactured red blood cells (mRBCs), are different to traditional biopharmaceutical products (the final product being the cells themselves as opposed to biological molecules such as proteins) and that presents a challenge of developing new robust and economically feasible manufacturing processes, especially for sample purification. Current purification technologies have limited throughput, rely on expensive fluorescent or magnetic immunolabeling with a significant (up to 70%) cell loss and quality impairment. To address this challenge, previously characterized mechanical properties of umbilical cord blood CD34+ cells undergoing in vitro erythropoiesis were used to develop an mRBC purification strategy. The approach consists of two main stages: (a) a microfluidic separation using inertial focusing for deformability‐based sorting of enucleated cells (mRBC) from nuclei and nucleated cells resulting in 70% purity and (b) membrane filtration to enhance the purity to 99%. Herein, we propose a new route for high‐throughput (processing millions of cells/min and mls of medium/min) purification process for mRBC, leading to high mRBC purity while maintaining cell integrity and no alterations in their global gene expression profile. Further adaption of this separation approach offers a potential route for processing of a wide range of cellular products. To address the challenge of stem‐cell‐derived red blood cells purification, we propose a label‐free approach to separate cells at high throughput based on their morphological (size) and mechanical (deformability) properties. The process consists of two main steps: (a) a microfluidic separation using inertial focusing in spiral microchannel and (b) membrane filtration.